Electron deficiency modulates hydrogen adsorption strength of Ru single-atomic catalyst for efficient hydrogen evolution. (July 2023) - Cao, Baoyue; Shi, Hu; Sun, Qiangqiang; Yu, Yan; Chang, Liangliang; Xu, Shan; Zhou, Chunsheng; Zhang, Hongxia; Zhao, Jianghong; Zhu, Yanyan; Yang, Pengju
Abstract: It was found that the Na modification is beneficial to the synthesis of Ru single-atomic catalyst anchored on GONa, which was prepared by one-step hydrothermal process. Importantly, the strong metal-support interaction facilitates the electron transfer from Ru SA to GONa via d-π conjugation, thus lowering the electron density of Ru SA. Experimental results and DFT calculations confirmed that the low electron density of Ru SA can significantly weaken the absorption of H* intermediates and simultaneously accelerate the desorption of generated H2 from catalyst surface. As a result, the Ru SA/GONa displayed exceptional HER activity with an extremely low over-potential of 20 mV at 10 mA cm −2, outperforming the benchmark commercial Pt (21 mV over-potential) and Ru nanoparticles (212 mV over-potential) catalysts. When Eosin Y was employed as a light harvester, this Ru SA/GONa achieves outstanding photocatalytic hydrogen production with a record-high apparent quantum efficiency of 65.2% at 520 nm. Moreover, single-atomic Pt, Pd, Au and Rh were also successfully anchored on the Na-functionalized GO support, suggesting the universality of Na-induced single-atomic synthesis. This work not only provides an effective method for the synthesis of single-atomic metal catalysts but also establishes the connection between the electronic structures of catalyst and performances.